Case report progressive multifocal leukoencephalopathy in hiv patient - Yensen Yestianto; Martin Firman Suryo (Institute of Computer Science (IOCS), 2023)
Progressive multifocal leukoencephalopathy (PML) is a neurological condition caused by the JC virus. PML is a demyelinating disease preferentially affecting the central nervous system. JC virus is a DNA virus of the polyomaviridae family. The virus remains latent in most immunocompetent hosts and rarely presents pathologically. In immunosuppressed hosts, however, a combination of poor cellular response of the host along with reactivation of the virus secondary to recombination of genes results in active disease. This case report described a 42 years old male patient with a HIV, PML, Anemia. The patient complaints that the body feels weak, loss of consciousness and difficult to communicate with. Physical examination, laboratory examination and MRI study findings was support the diagnosis of PML in HIV patients. This case report described a 42 years old male patient with a HIV, PML, Anemia. The patient complaints that the body feels weak, loss of consciousness and difficult to communicate with. Physical examination, laboratory examination and MRI study findings was support the diagnosis of PML in HIV patients.